Adrenoleukodystrophy: A Rare Case Report - Mondol, MBA; Siddiqui, MMR; Wahab, L; Hoque, MA; Khan, SU; Rahman, KM; Mohammad, QD (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A young boy of 18 years was admitted at department of Neurology, Dhaka Medical College Hospital with the complaints of progressive generalized hyper-pigmentation, gradual loss of vision, hearing impairment, abnormal behaviors and one episode of seizure. Examination finding revealed, abnormal behaviors, generalized hyper pigmentation of skin, oral mucosa, gum, tongue and palmer creases. He has diffuse hair loss, bilateral primary optic atrophy, bilateral sensoryneural deafness. All routine investigations revealed normal findings except, CSF protein were elevated, biochemical features (very high ACTH, low basal cortisol) of primary adrenal failure, Magnetic resonance imaging (MRI) of the head showed bilateral symmetrical white matter abnormalities in parieto-occipital regions. The diagnosis of Adreno-leukodystrophy (ALD) was strongly suggested from the medical history, biochemical and radiological (MRI) findings of brain. The purpose of our report is to highlight this very rare nontreatable disease to all. A patient of neuropsychiatric symptoms with Addison's disease we must think about ALD, because it's progression can be delayed with early diagnosis and supportive treatments, it's incidence can be reduced by genetic counseling. Key words: Adrenoleukodystrophy (ALD); Addison's disease; Very long chain fatty acid (VLCFA). DOI: 10.3329/jbcps.v28i3.6514 J Bangladesh Coll Phys Surg 2010; 28: 189-192